CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING THE MERDEKA CURRICULUM IN LANGUAGE EDUCATION: A META-SYNTHETIC ANALYSIS - Emawati, Emawati; Taufiqulloh, Taufiqulloh; Fadhly, Fahrus Zaman (University of Kuningan, 2024)
The Merdeka Curriculum, recently introduced in Indonesia, aims to restore learning by prioritizing essential content and character development. While promising, its implementation in language education presents significant challenges and opportunities. This meta-synthetic analysis explores these aspects by synthesizing findings from various qualitative studies on the curriculum’s impact on language learning. Data were gathered from peer-reviewed journals, conference proceedings, and educational reports, focusing on studies conducted in diverse Indonesian educational settings. Key challenges identified include inconsistent teacher training, limited resources, and resistance to new pedagogical approaches. However, the curriculum also offers notable opportunities, such as enhanced student engagement, improved critical thinking, and the promotion of learner autonomy. Its emphasis on project-based learning and flexible teaching methods fosters a more interactive, student-centered environment. The study concludes that while the Merdeka Curriculum presents challenges, it also holds significant potential to enhance language education. Addressing these challenges requires comprehensive teacher training, adequate resource allocation, and continuous support for educators. The study recommends targeted professional development for teachers, increased investment in educational resources, and ongoing evaluation to ensure effective implementation. Policymakers should create supportive frameworks that enable schools to adapt the curriculum to their specific contexts, maximizing its benefits for language education.